1995
DOI: 10.1021/bi00037a026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Calponin Binding to Actin

Abstract: Calponin, a protein isolated from smooth muscle and nonmuscle cells, has previously been shown to inhibit the actin-activated ATPase activity of myosin. Reports of the stoichiometry of binding range from 1 calponin per actin to 1 calponin per 3 actin monomers. We now report a detailed study of the binding of [14C]iodoacetamide-labeled calponin to actin. The labeling procedure did not significantly alter the binding constant of calponin to actin. The stoichiometry of binding was variable and dependent on ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
36
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 59 publications
13
36
4
Order By: Relevance
“…Also, under the conditions used, the actin was saturated by a -actinin when the molar ratio for a -actinin/G-actin in the incubation mixture was 0.25-0.30. These results agree with the data reported in the literature (15,16).…”
Section: Resultssupporting
confidence: 93%
“…Also, under the conditions used, the actin was saturated by a -actinin when the molar ratio for a -actinin/G-actin in the incubation mixture was 0.25-0.30. These results agree with the data reported in the literature (15,16).…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained in the Chalovich laboratory (8). This suggested that calponin and caldesmon do not form a mutual complex on actin and reside on different populations of thin filaments in vivo.…”
supporting
confidence: 84%
“…The higher affinity between calponin and immobilized actin (8 nM, Figure 4B) in comparison with that previously reported (6 µM, [42]) may be due to the nature of the solid-phase assay conditions, which may facilitate the formation of the F-actin-calponin complex. Although detectable by the ELISA experiments, the binding between calponin and immobilized tropomyosin is significantly weaker in contrast to the binding to actin ( Figure 4A).…”
Section: Phosphorylation Of Serine-175 Reduces Calponin's Actin-bindicontrasting
confidence: 43%